Primary aldosteronism as an endocrinological challenge – old doubts and new diagnostic possibilities - Cyrańska-Chyrek, Ewa; Grzymisławska, Małgorzata; Ruchała, Marek (Journal of Medical Science, 2016)
Hypertension constitutes a common clinical problem worldwide. In fact, a systematic increase in its detection is predicted in the following years, with early detection, accurate diagnosis and effective treatment of hypertension being a priority. The most common endocrinological cause of hypertension is primary aldosteronism. What is more, elevated aldosterone levels cause a deterioration in blood pressure normalization, diabetes, and significantly increase cardiovascular risk. There are two distinct causes of primary aldosteronism – aldosterone producing adenoma (APA), as well as bilateral adrenal hyperplasia (BAH) and proper differentiation between APA and BAH has clinical implications. In the case of the former adrenalectomy is advised, whereas the latter is followed by introduction of proper pharmacotherapy with aldosterone antagonists (spironolactone, eplerenone).
Keywords: primary aldosteronism; adrenal tumor; aldosterone producing adenoma; bilateral adrenal hyperplasia; adrenal CT; adrenal venous sampling